IMPLEMENTASI MEDIA BAHASA DALAM PEMBELAJARAN MAHĀRAT AL-KALĀM BERDASARKAN FUNGSI MEDIA PEMBELAJARAN MENURUT KEMP DAN DAYTON - Isop Syafe'i (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2020)
The purpose of this study was (1) to find out the language media in Mahārat al-Kalām learning (2) to find out the function of learning media according to Kemp and Dayton (3) to find out the language media in learning Mahārat al-Kalām Tsanawiyah Madrasah based on the function of instructional media according to Kemp and Dayton. This study uses a descriptive method with a qualitative approach, the researcher as a key instrument, data analysis is inductive, and the results of the study emphasize the meaning rather than the generalization of objects. Data collection techniques used were observation, in-depth interviews, and documentation. The findings of this study are: First, the language media that can be used by teachers in learning Mahārat al-Kalām are: Analogy, Antonyms, Synonyms, Give examples, Direct instruction, repeating words and sentences, and question and answer. Second, the function of learning media according to Kemp and Dayton, namely: motivating interests and actions, presenting information, and giving instructions. Third, there is a significant relationship between language media and the function of learning media according to Kemp and Dayton, so that it can be known the steps of learning by using language media in learning Mahārat al-Kalām.